Primary pulmonary leiomyosarcoma: review of the literature and case report - López Alvarado Mariela Itzayana; Guerrero Gómez Alan; Carmona Flores Oscar (International Journal of Research in Medical Sciences, 2023)
Primary pulmonary leiomyosarcoma (PPL) is an extremely rare malignant tumor. It has been revealed that PPL may originate from the smooth muscle of the pulmonary parenchyma, pulmonary arteries and bronchi. Patients with PPL may be asymptomatic or present with symptoms similar to those observed in other primary lung tumors. The present study reports the case of a 21-year-old woman who presented with orthopnea, medium effort dyspnea, so an extension study computed tomography (CT) is performed, finding a left thoracic tumor. Where a percutaneous biopsy is performed, concluding PPL, by image, it is considered unresecable due to pericardial infiltration, and it is sent to cycle of chemotherapy. Currently completed treatment with partial response to it, due to findings by image, ECOG and patient age, a case session is decided, and panpleuronectomy was performed.